2023
DOI: 10.1088/1741-2552/acbf79
|View full text |Cite
|
Sign up to set email alerts
|

Modeling extracellular stimulation of retinal ganglion cells: theoretical and practical aspects

Abstract: Objective. Retinal prostheses use electric current to activate inner retinal neurons, providing artificial vision for blind people. Epiretinal stimulation primarily targets retinal ganglion cells (RGCs), which can be modelled with cable equations. Computational models provide a tool to investigate the mechanisms of retinal activation, and improve stimulation paradigms. However, documentation of RGC model structure and parameters is limited, and model implementation can influence model predictions. Approach. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…We later found that ultrasound images, which we used to locate electrical ground, did not affect model predictions. Another improvement to our prior study was implementing a mammalian RGC model with dendrites that we optimized for run-time based on our sensitivity analysis, as opposed to a simpli ed, amphibian RGC model 29 Future work could apply this modelling framework to other retinal prostheses. In addition, we could apply optimization paradigms to these models to program patient-speci c stimulation settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We later found that ultrasound images, which we used to locate electrical ground, did not affect model predictions. Another improvement to our prior study was implementing a mammalian RGC model with dendrites that we optimized for run-time based on our sensitivity analysis, as opposed to a simpli ed, amphibian RGC model 29 Future work could apply this modelling framework to other retinal prostheses. In addition, we could apply optimization paradigms to these models to program patient-speci c stimulation settings.…”
Section: Discussionmentioning
confidence: 99%
“…The cable equations for RGC membrane dynamics are described in detail in our prior publication, and our biophysical model is open-source on GitHub 29 . Brie y, we determined the extracellular potential at the center of each neuron compartment from the FEM solution.…”
Section: Statistical Models For Perceptual Thresholdmentioning
confidence: 99%
“…We therefore use the general term 'focal activation' in this work. The AIS represents the section of RGCs with the highest sodium channel density and therefore the lowest local stimulation threshold (Fried et al 2009, Werginz et al 2020, Kish et al 2023, Radivojevic et al 2016. Therefore, the most natural conclusion is that the focal activation reported here happens with the AIS in close proximity to the stimulation electrodes and the two different cellular compartments AIS and distal axon, have different strength-duration relationships.…”
Section: The Mechanism Underlying Focal Activation With Sinusoidal St...mentioning
confidence: 99%
“…Moreover, both classes (i.e., BC and RGC) of retinal neurons are known to have numerous subtypes [72,73]; their unique sensitivities and morphological differences should be considered in the numerical stimulations. Eventually, it would be imperative to test the penetrating electrode structures presented in our modeling study in ex-/invivo additional experiments and/or extra cellular-level simulations using NEURON [36,74]. This comprehensive approach will provide a more accurate representation of the neural responses to electrical stimulation in the retina.…”
Section: B Limitation Of Our Studymentioning
confidence: 99%